Tradition, change and social reform in the fatwas of the Imam Muhammad 'Abduh - Badrawi, Malak Tewfik (AUC Knowledge Fountain, 2017)
This thesis proposes to examine some of the fatwas, or legal opinions, issued by Muhammad ‘Abduh, and taken from the manuscript ledgers at Dār al-Iftā’ al-Miṣriyah. The fatwas involve official and semi-official issues, problems of personal status, financial matters, and relations with others. They were picked for their clarity, peculiarity, diversity, and will be examined for their relevance to the needs of various groups of society at that time and for the legal argumentation used. The fatwas will be examined to try to determine ‘Abduh’s legal approach, and his methodology when dealing with everyday issues. Fatwas are also useful tools to gauge different trends and tendencies in a society. The queries reflect some of the preoccupations of individuals. As for the responses, whether these are timely or untimely, or whether they are mundane or peculiar, they demonstrate the degree of empathy of the mufti with the public. Indeed, Muhammad ‘Abduh once observed that the ‘ulamā’- Muslim religious scholars- of his time, even if they were highly qualified, were totally isolated from the needs of the public, and that the only interaction the community had was with the storytellers that they called preachers at the Friday prayers. Such a statement implied that he considered that the function of the religious scholars was to serve society.